2019
DOI: 10.1108/imr-03-2017-0057
|View full text |Cite
|
Sign up to set email alerts
|

Institutional environment and network competence in successful SME internationalisation

Abstract: This study examines the impact of institutional environment on the international performance of small-and medium-sized enterprises (SMEs) and how this relationship is influenced by network competence. Design/methodology/approach: This study uses a quantitative approach. In total, 119 internationally operating Finnish SMEs from five industry sectors are sampled via a crosssectional survey. Data are analysed through regression modelling. Findings: The international performance of SMEs is influenced directly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 142 publications
(199 reference statements)
3
90
0
8
Order By: Relevance
“…We also classified the studies we investigated by continent (Figure ). Most of the research studies we have found occur in Europe, which makes up 41% of the research (e.g., Girgenti, Peano, Baudino, & Tecco, ; Hertel & Menrad, ; Flynn & Davis, ; Jansson, Nilsson, Modig, & Hed Vall, ; Mayr, Mitter, & Aichmayr, ; Torkkeli, Kuivalainen, Saarenketo, & Puumalainen, ; Girella, Zambon, & Rossi, ), Asia accounts for 22% (e.g., Seth, Rehman, & Shrivastava, ; Singh, Olugu, & Musa, ) and South America at 19% (e.g., Lucato, Costa, & de Oliveira Neto, ; Pacheco, Caten, Jung, Navas, & Cruz‐Machado, ; Sarango‐Lalangui, Álvarez‐GarcĂ­a, & del RĂ­o‐Rama, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also classified the studies we investigated by continent (Figure ). Most of the research studies we have found occur in Europe, which makes up 41% of the research (e.g., Girgenti, Peano, Baudino, & Tecco, ; Hertel & Menrad, ; Flynn & Davis, ; Jansson, Nilsson, Modig, & Hed Vall, ; Mayr, Mitter, & Aichmayr, ; Torkkeli, Kuivalainen, Saarenketo, & Puumalainen, ; Girella, Zambon, & Rossi, ), Asia accounts for 22% (e.g., Seth, Rehman, & Shrivastava, ; Singh, Olugu, & Musa, ) and South America at 19% (e.g., Lucato, Costa, & de Oliveira Neto, ; Pacheco, Caten, Jung, Navas, & Cruz‐Machado, ; Sarango‐Lalangui, Álvarez‐GarcĂ­a, & del RĂ­o‐Rama, ).…”
Section: Resultsmentioning
confidence: 99%
“…We also classified the studies we investigated by continent ( Figure 4). Most of the research studies we have found occur in Europe, which makes up 41% of the research (e.g., Girgenti, Peano, Baudino, & Tecco, 2014;Hertel & Menrad, 2015;Flynn & Davis, 2016;Jansson, Nilsson, Modig, & Hed Vall, 2017;Mayr, Mitter, & Aichmayr, 2017;Torkkeli, Kuivalainen, Saarenketo, & Puumalainen, 2019;Girella, Zambon, & Rossi, 2019), Asia accounts for 22% (e.g., Seth, Rehman, & Shrivastava, 2018;Singh, Olugu, & Musa, 2016) and South America at 19% (e.g., Lucato, Costa, & ables on which SMEs can be categorized (Bar, 2015;Boiral, Ebrahimi, Kuyken, & Talbot, 2019;Groot et al, 2019;Long, Looijen, & Blok, 2018;Malesios et al, 2018;Prieto-Sandoval, Ormazabal, Jaca, & Viles, 2018). Our results show the pattern in the sectors that are studied from 2013 to 2019 (Figure 7).…”
Section: And Eco-friendly and Driversmentioning
confidence: 99%
“…They found that the performance of institute affiliates was significantly affected by their network abilities. Torkkeli, et al [29] found that networking capabilities help develop knowledge-intensive products that enable companies to identify and take advantage of performance opportunities in global markets.…”
Section: Network Servicesmentioning
confidence: 99%
“…Thus, institutional theory has played a key role in explaining institutional factors behind entrepreneurial success particularly with respect to international topics (Bruton et al 2010;Jones et al 2011;Lim et al 2010). Indeed, the relationship between institutional conditions and entrepreneurial internationalization has been studied extensively (Child et al 2017;Ervits and Zmuda 2018;Oparaocha 2015;Torkkeli et al 2019). Favorable institutional conditions are related to international performance of entrepreneurial firms (Torkkeli et al 2019) and account to global innovation (Ervits and Zmuda 2018).…”
Section: Institutional Environment and Eomentioning
confidence: 99%
“…Indeed, the relationship between institutional conditions and entrepreneurial internationalization has been studied extensively (Child et al 2017;Ervits and Zmuda 2018;Oparaocha 2015;Torkkeli et al 2019). Favorable institutional conditions are related to international performance of entrepreneurial firms (Torkkeli et al 2019) and account to global innovation (Ervits and Zmuda 2018). Institutions such as government agencies, business incubators, research institutes or agencies for international development help to overcome resource barriers and support IE activity (Oparaocha 2015).…”
Section: Institutional Environment and Eomentioning
confidence: 99%